Declining Processes of the World - Khan,Peter J.
The condition of the world today, which is in a state of decline from negative forces, requires that both Bahá'ís and others make drastic changes in certain fundamental attitudes.
Title given for this online copy of the talk; original title not known. Date and location of this talk not known; contact me if you know.